IMPLICATIONS OF THE SEISMIC SOURCE DYNAMICS FOR THE CHARACTERISTICS OF A POSSIBLE TSUNAMI IN A MODEL PROBLEM OF THE SEISMIC GAP IN THE CENTRAL KURILE REGION - Lobkovsky L.I.; Baranov B.V.; Mazova R.Kh.; Kataeva L.Yu. (My University, 2006)
Various scenarios of earthquakes and the associated tsunami wave generation are numerically simulated. It is shown that, depending on the chosen dynamic source parameters in the central seismic gap zone of the Kurile-Kamchatka arc, the characteristics of tsunami waves in the water area of the Sea of Okhotsk and Kurile-Kamchatka zone can differ dramatically, from insignificant inundation of Sakhalin and Kamchatka coasts to a catastrophic run-up of waves up to 8 m in height. Detailed numerical constraints on the tsunami wave run-up are obtained for a number of points of the Sakhalin coastline, the form of the first waves climbing the coast is determined, and the run-up velocity characteristics are computed.
Keywords: TSUNAMI GENERATION; SUBMARINE LANDSLIDE; SEDIMENTARY MASS; ELASTOPLASTIC MODEL; SHALLOW WATER EQUATIONS